Assessment of the Tourism Potential of Kashkadarya and the Principles of its Development (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
In this article, the possibilities of tourism in Kashkadarya region are discussed over the years, and proposals that can be put into practice in the future are presented.